2019
DOI: 10.15403/jgld-182
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Probiotics and Prebiotics in Prevention of Infectious Complications Following Hepatic Resections: Systematic Review and Meta-Analysis

Abstract: Background & Aims: Infections occurring after hepatic resection cause significant morbidity, mortality, and prolonged hospitalization. Probiotics and prebiotics are considered to offer protection against post-operative infections. We aimed to determine the effect of probiotics and prebiotics on the post-operative infection rate after hepatic resection by conducting a systematic review and a meta-analysis. Method: We searched various databases, namely, the PubMed, Medline, Embase, and Cochrane Controlled Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Although this review is directed at the antimicrobial role of probiotics in combating wound infections and has shown promising results as possible alternatives or adjuvant therapies, the problem is still more complex. In order to achieve optimal wound healing, it is necessary to address in parallel additional factors regarding the patient's general health or the wound's physical environment and the body's immune response [23,151]. Despite the fact that it is known that wound healing is impaired by wound infection, the exact role of probiotics in delayed wound healing remains controversial due to discrepancy in clinical results [14,64,152].…”
Section: Resultsmentioning
confidence: 99%
“…Although this review is directed at the antimicrobial role of probiotics in combating wound infections and has shown promising results as possible alternatives or adjuvant therapies, the problem is still more complex. In order to achieve optimal wound healing, it is necessary to address in parallel additional factors regarding the patient's general health or the wound's physical environment and the body's immune response [23,151]. Despite the fact that it is known that wound healing is impaired by wound infection, the exact role of probiotics in delayed wound healing remains controversial due to discrepancy in clinical results [14,64,152].…”
Section: Resultsmentioning
confidence: 99%
“…Surgical stress-related dysbiosis leads to bacterial translocation resulting in a limited detoxification function of the liver being the central hub of the gut–liver axis, increased susceptibility to infections, and worse outcome. After liver surgery, about 30% of the patients develop a bacterial infection, and if bacteremia occurs, the risk of liver failure increases to over 50% and mortality to over 40% [ 1 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…LR, which is especially performed for tumors, is associated with both mortality and morbidity of 3.5% and 10–15%, respectively [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. About 30% of patients develop a bacterial infection and about 10% intra-abdominal sepsis, mostly caused by enterogenic bacteria after LR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general acceptance of the health benefits of prebiotics is based upon metabolic and immunological end-points, but these have seldom been backed up by quality data on healthrelated outcomes in clinical trials in most areas of study, as shown in systematic reviews in several areas of health promotion [11,[13][14][15][16][17][18][19][20][21]. The difficulty in showing benefits might, as discussed above, relate to the lack of consideration to background diet in the design of trials, or it might relate to the fact that the concept is overblown and benefits may be very modest indeed.…”
Section: Author Manuscriptmentioning
confidence: 99%